Health Psychology in Brazil - Gorayeb, Ricardo (2010)
This article presents a description of the development of Health Psychology in Brazil from the author´s viewpoint, reporting his experiences in the area, since his undergraduate studies until nowadays. The author’s learning experiences with professors that were relevant to the development of Psychology and Health Psychology in the country are emphasized. Some misunderstood terms, such as Health Psychology x Clinical Psychology x Psychology in Hospitals are analyzed. This paper also evaluates the scientific production in the area, as well as ways to increase such production. Finally, an analysis of the instruments needed to develop the area is performed, pointing out some research groups working in evidence-based Health Psychology in Brazil, and presenting a perspective of growth of the area.